فاعلية برنامج تدريبي قائم على انموذج شوارتز في تنمية كفاءة الأداء عند معلمي مادة التربية الإسلامية - الزبيدي، رعد خلف محمد; الجبوري، عبدالمهيمن محمود حمد (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2021)
The current research aims to identify the effectiveness of a training program based on the Schwartz model in developing performance efficiency among teachers of Islamic education. The researcher approved the design of the experimental group randomized selection with pre and posttest in order to know the effectiveness of the training program in developing performance efficiency the researcher prepared one tool to measure the variables of his research. The tool is the observation card form to evaluate the performance of Islamic education teachers and it consisted of (53) paragraphs that the researcher verified of their validity and stability after presenting them to a group of arbitrators. and after analyzing the results statistically, the researcher reached the following: 1- The presence of a statistically significant difference at a significance level (0.05) between the mean scores of the experimental group teachers who studied using the training program before and after the experiment in the observation card.
يهدف البحث الحالي التعرف على فاعلية برنامج تدريبي قائم على أنموذج شوارتز في تنمية كفاءة الأداء عند معلمي مادة التربية الإسلامية، اعتمد الباحث تصميم المجموعة التجريبية العشوائية الاختيار ذات الاختبار القبلي والبعدي من أجل تعرف فاعلية البرنامج التدريبي في تنمية كفاءة الأداء، اختار الباحث عينة من معلمي التربية الإسلامية في قضاء العلم وتم اختيار عينة عشوائية بلغت (٥٠) معلما، أخضعوا للبرنامج التدريبي ضمن دورة تدريبية لمدة ثلاثة أشهر، ولغرض معرفة فاعلية البرنامج التدريبي أعد الباحث أداة لقياس متغير بحثه استمارة بطاقة الملاحظة لتقويم أداء معلمي التربية الإسلامية وتألفت من (53) فقرة تحقق الباحث من صدقها وثباتها بعد عرضها على مجموعة من المحكمين، (SPSS) استخدم للتحليل وتوصل الباحث إلى ما يأتي: ١- وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0,05) بين متوسطي درجات معلمي المجموعة التجريبية الذين درسوا باستعمال البرنامج التدريبي قبل التجربة وبعدها في بطاقة الملاحظة.
Keywords: البرامج التدريبية -- النماذج التدريسية -- الكفايات المهنية -- التربية الإسلامية